2008
DOI: 10.1016/j.ajodo.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and posttreatment skeletal effects of rapid maxillary expansion studied with low-dose computed tomography in growing subjects

Abstract: Introduction:The aim of this study was to apply low-dose computed tomography (CT) to evaluate treatment and posttreatment effects produced by rapid maxillary expansion (RME) at the levels of the midpalatal suture and the pterygoid processes. Methods: A sample of 17 subjects (7 boys, 10 girls; mean age, 11.2 years) was analyzed. Multi-slice CT scans were taken before RME, at the end of the active expansion phase, and after a retention period of 6 months. Statistical analysis was performed with ANOVA for repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 13 publications
4
88
2
7
Order By: Relevance
“…This difference in density explains the greater opening in the anterior vs the posterior sutural regions after the active phase of expansion, as demonstrated in a previous study. 9 Lione et al 9 reported that the amount of transverse increase at the middle sutural width (corresponding to PS ROI in our study) was about 70% of that observed in the anterior sutural width (corresponding to AS ROI in our study).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This difference in density explains the greater opening in the anterior vs the posterior sutural regions after the active phase of expansion, as demonstrated in a previous study. 9 Lione et al 9 reported that the amount of transverse increase at the middle sutural width (corresponding to PS ROI in our study) was about 70% of that observed in the anterior sutural width (corresponding to AS ROI in our study).…”
Section: Discussionmentioning
confidence: 79%
“…6 Recently, the opening of the midpalatal suture after RME was evaluated with computed tomography (CT), which provides accurate 3-dimensional assessment of skeletal changes. [7][8][9] The use of CT has been proposed also for the quantitative evaluation of bone density with the Hounsfield index in selected regions of interest (ROI). 10 The same index has been used to assess bone density for implant placement in the maxillary bones.…”
mentioning
confidence: 99%
“…5,19 For the standardized 5-mm activation, the mean expansion between the Mx6s was approximately 4.3 mm (86%) for the bonded (McNamara-type) RME patients compared to 4.0 mm (80%) in the banded (Hyrax-type) groups (Table 1). This relatively efficient RME may reflect the concurrent expansion of the lower arch.…”
Section: Discussionmentioning
confidence: 99%
“…There are many 2D reports indicating a nonparallel, triangular expansion pattern: greater expansion in the anterior rather than the posterior dimension. 19,20,33 However, there have been only a few studies that have focused on the effects of RME on craniofacial sutures by evaluating the frontal (coronal) dimension. [34][35][36][37] Overall, the present literature review suggests the bonded appliance is the optimal appliance before the maxillary first premolars (Mx4s) erupt, and the banded expander is more desirable thereafter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation